PERBANDINGAN PERILAKU MORAL ANAK KELOMPOK B YANG MENGIKUTI TK A DAN YANG TIDAK MENGIKUTI TK A DI TAMAN KANAK – KANAK PERMATA KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Zulfa Reni; Zulkifli Zulkifli; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: This research purposed is to know comparison of the moral behavior of group B's children who attend TK A and those who did not take TK A in kindergarten Permata Kecamatan Tebing Tinggi Kabupaten Kepulauan Meranti. The samples in this study were all children in group B’s which consist 90 children. The sample in this study was divided into two, namely children who attended TK A with a total of 33 children while children who did not attend TK A which are 57 children. This study used comparative method to see if there is comparison between children who attended TK A and those who did not attend TK A. The data collection technique used is observation. The data analysis technique uses the Paired Samples Test hypothesis and statistical method analysis with the SPSS program for Windows Ver. 16. Based on hypothesis test result obtained t count equal to 12,96. This shows that there is a difference between the moral behavior of group B’s children who participated in TK A and those who did not participate TK A in kindergartens Permata Mecamatan Tebing Tinggi Kabupaten Kepulauan Meranti. If there is any difference between t test and t test table then Ha is accepted and H0 is rejected. To prove the difference between between the moral behavior of group B’s children who participated in TK A and those who did not participate TK A in kindergartens Permata Mecamatan Tebing Tinggi Kabupaten Kepulauan Meranti. can be tested